Design and Development of Long-term Care Management System Based on Internet of Things - Yang, Yu-Qiang; Lu, Chien-Yu; Hsieh, Hsiu-Ying; Chang, Tsung-Chieh; Su, Te-Jen (Sensors and materials, 2021)
The aim of this study is to design and establish a long-term care management system with the functions of data acquisition, data access, and website management for a long-term care center, along with the utilization of an Internet of Things (IoT) demo board and router to transmit the measurement parameters of biomedical sensor modules to the server database, including blood pressure, body temperature, and heart rate modules, for physiological information measurement by the system. The interface for information browsing is simple and user-friendly. This system uses Windows 10 as its operating system and uses Apache to create a Hypertext Transfer Protocol (HTTP) server, as well as the MySQL relational database management system and WordPress.com blog services. WordPress.com is also utilized to design a web interface so that the family of the person in long-term care can instantly access their physiological information, and the hierarchical webpage architecture enables administrators to manage the information regarding long-term care. The blog format allows users to operate it easily, and the physiological data and website information are stored in the MySQL system. Message Queuing Telemetry Transport (MQTT) protocol was designed by using Microsoft Visual C# to store the data in the database with the application programs to implement the transmission function for the physiological data. A WeMos D1 demo board is utilized to implement the data publish function for heart rate, body temperature, and blood pressure via the MQTT protocol. The advantage of this system is that it is based on the IoT structure, and the biomedical measurement data can be managed via the website with security, privacy, wear ability, and low-power operation. Moreover, an alarm function is also implemented to help medical staff manage measurement data and achieve the goal of instant care.